Demographic and Occupational Risk Factors Associated With Suicide-Related Aeromedical Evacuation Among Deployed U.S. Military Service Members. Issue 11 (30th December 2020) - Straud, Casey L; Moore, Brian A; Hale, Willie J; Baker, Monty; Gardner, Cubby L; Shinn, Antoinette M; Cigrang, Jeffrey A; Litz, Brett T; Mintz, Jim; Lara-Ruiz, Jose M; Young-McCaughan, Stacey; Peterson, Alan L; et al.
ABSTRACT: Introduction: Suicide is a significant problem in the U.S. military, with rates surpassing the U.S. general population as of 2008. Although there have been significant advances regarding suicide risk factors among U.S. military service members and veterans, there is little research about risk factors associated with suicide that could be potentially identified in theater. One salient study group consists of service members who receive a psychiatric aeromedical evacuation out of theater. The primary aims of this study were as follows: (1) determine the incidence of suicide-related aeromedical evacuation in deployed service members, (2) identify demographic and military characteristics associated with suicide-related aeromedical evacuation, and (3) evaluate the relationship between suicide-related aeromedical evacuation from a deployed setting and military separation. Materials and Methods: This was an archival analysis of U.S. Transportation Command Regulating and Command and Control Evacuation System and Defense Manpower Data Center electronic records of U.S. military service members (N = 7023) who were deployed to Iraq or Afghanistan and received a psychiatric aeromedical evacuation out of theater between 2001 and 2013. χ 2 tests of independence and standardized residuals were used to identify cells with observed frequencies and proportions, respectively, that significantly differed from what would be expected by chance. In addition, odds ratios were calculated to provide context about the nature of any significant relationships. Results: For every 1000 psychiatric aeromedical evacuations that occurred between 2001 and 2013, 34.4 were suicide related. Gender, ethnicity, branch of service, occupation classification, and deployment theater were associated with suicide-related aeromedical evacuation (odds ratios ranged from 1.37 to 3.02). Overall, 53% of all service members who received an aeromedical evacuation for any psychiatric condition had been separated from the military for a variety of reasons (both voluntary and involuntary) upon record review in 2015. Suicide-related aeromedical evacuation was associated with a 37% increased risk of military separation compared to evacuation for another psychiatric condition ( P < 0.02). Conclusions: Findings provide novel information on risk factors associated with suicide-related aeromedical evacuation as well as military separation following a suicide-related aeromedical evacuation. In many cases, the psychiatric aeromedical evacuation of a service member for suicidal ideations and their subsequent separation from active duty is in the best interest of the individual and the military. However, the evacuation and eventual military separation can be costly for the military and the service member. Consequently, the military should focus on indicated prevention interventions for individuals who show sufficient early signs of crisis and functional problems so that specialized interventions can be used in theater to prevent evacuation. Indicated prevention interventions should start with leaders' awareness and mitigation of risk and, when feasible, evidence-based interventions for suicide risk provided by behavioral health (eg, brief cognitive behavioral therapy for suicide). Future research should evaluate the feasibility, safety, and efficacy of delivering suicide-related interventions in theater.